(untitled) ("Temas Sociais" Journal, 2022)
This article seeks to understand the quality of the Home Support Service (HSS) in the Municipality of Vagos, Portugal, based on the degree of satisfaction, from the perspective of customers and employees. The study involved 80 customers and 50 employees from nine institutions in the municipality of Vagos with HSS. We used a quantitative methodological approach, and the data collection was accomplished through a questionnaire survey, including the sociodemographic characterization of these two sample groups, and the application of the official Social Security HSS satisfaction questionnaire. This instrument comprises 62 questions that characterize the degree of satisfaction of the HSS in five areas: Facilities, Equipment and Signage; Reliability/Credibility; Technical competence; Responsibility and responsiveness; Service and Communication. Some of the most relevant results obtained allow us to state that both groups in the sample rated HSS as high, however, customers have a higher average in four of these five areas, compared to employees.